Factors affecting the succes of creative economy based micro small medium business in the city of Semarang - Fidyah Yuli Ernawati; Marsha Ayunita Irawati; Arini Novandalina (Institute of Computer Science (IOCS), 2023)
This research was conducted aiming to look at the factors that influence the success of micro, small and medium enterprises based on innovative economy in the city of Semarang. This can be seen from the key factor in fulfilling MSMEs based on a creative financial system in the form of the progress of MSMEs in the city of Semarang today. The population in this study were 50 SMEs in the city of Semarang. The data series strategy in this study, the use of the note series strategy through questionnaires, and documentation shows that the advertising variables on the fulfillment of SMEs and the creative economy system have insignificant results. The results of this study indicate that all logo variables on the achievement of SMEs and innovative financial systems have great results.